Некоторые компоненты интеллектуальной системы "Управление_ТЭП" - Писаренко, Ю.В.; Мелкумян, Е.Ю. (Комп’ютерні засоби, мережі та системи, 2014)
An overview of some components of the developed intelligent system "CONTROL _TEP" using intelligent robots is considered.